2022
DOI: 10.3390/ijerph192215329
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 Pandemic Led to Changes in the Tasks of the Primary Care Workforce? An International Survey among General Practices in 38 Countries (PRICOV-19)

Abstract: The COVID-19 pandemic has had a large and varying impact on primary care. This paper studies changes in the tasks of general practitioners (GPs) and associated staff during the COVID-19 pandemic. Data from the PRICOV-19 study of 5093 GPs in 38 countries were used. We constructed a scale for task changes and performed multilevel analyses. The scale was reliable at both GP and country level. Clustering of task changes at country level was considerable (25%). During the pandemic, staff members were more involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…According to our findings, since the COVID-19 pandemic, staff members of PC practices have been more involved and proactive in patient care, as well as in distributing work in the case that a staff member in practice is missing owing to COVID-19 infection/quarantine. This is in line with the findings of the Groenewegen et al study, indicating that PC practices also changed the tasks of healthcare personnel in response to the needs for care during the COVID-19 pandemic [ 38 ]. Many PRICOV study participants agreed that their responsibilities had increased and that GPs and GP trainees were more involved in proactively reaching out to patients who might delay seeking healthcare [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to our findings, since the COVID-19 pandemic, staff members of PC practices have been more involved and proactive in patient care, as well as in distributing work in the case that a staff member in practice is missing owing to COVID-19 infection/quarantine. This is in line with the findings of the Groenewegen et al study, indicating that PC practices also changed the tasks of healthcare personnel in response to the needs for care during the COVID-19 pandemic [ 38 ]. Many PRICOV study participants agreed that their responsibilities had increased and that GPs and GP trainees were more involved in proactively reaching out to patients who might delay seeking healthcare [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the findings of the Groenewegen et al study, indicating that PC practices also changed the tasks of healthcare personnel in response to the needs for care during the COVID-19 pandemic [ 38 ]. Many PRICOV study participants agreed that their responsibilities had increased and that GPs and GP trainees were more involved in proactively reaching out to patients who might delay seeking healthcare [ 38 ]. However, pandemics are high-stakes situations, and PC workers should frequently manage difficult and unacknowledged burdens of responsibility.…”
Section: Discussionsupporting
confidence: 89%
“…There has been some major change in healthcare workers' decision-making in times of uncertainty in particular when allocating resources within this challenging clinical situation (29,30). This certainly has led to an impact on both the physical and mental health needs of healthcare workers, fears of transmitting the virus to family members, and lack of personal protection equipment, which has certainly led depleted workforce (31)(32)(33)(34)(35)(36).…”
Section: Effects On Healthcare Staff Well-beingmentioning
confidence: 99%
“…Decision-making during a non-pandemic environment can be in itself challenging for most healthcare workers. However, with the supplement of a pandemic, it has certainly added a new dimension to how decision-making in times of uncertainty is managed and has since been quite difficult for some healthcare workers when allocating resources within this challenging clinical situation [29,30]. This extra burden has certainly played a role in both the physical and mental health needs of healthcare workers [31].…”
Section: Future Of Primary Care Post-pandemicmentioning
confidence: 99%
“…Although the merits of outreach work are widely acknowledged [ 13 , 22 ], the implementation in practice is regarded as challenging [ 13 , 23 , 24 , 25 , 26 ]. For example, previous evidence demonstrated that several practice characteristics are decisive in setting up outreach work.…”
Section: Introductionmentioning
confidence: 99%